Peri-intubation cardiac arrest in the Emergency Department: A National Emergency Airway Registry (NEAR) study. (May 2021) - April, Michael D.; Arana, Allyson; Reynolds, Joshua C.; Carlson, Jestin N.; Davis, William T.; Schauer, Steven G.; Oliver, Joshua J.; Summers, Shane M.; Long, Brit; Walls, Ron M.; Brown, Calvin A.; ,; et al.
Abstract: Aim: To determine the incidence of peri-intubation cardiac arrest through analysis of a multi-center Emergency Department (ED) airway registry and to report associated clinical characteristics. Methods: This is a secondary analysis of prospectively collected data (National Emergency Airway Registry) comprising ED endotracheal intubations (ETIs) of subjects >14 years old from 2016 to 2018. We excluded those with cardiac arrest prior to intubation. The primary outcome was peri-intubation cardiac arrest. Multivariable logistic regression generated adjusted odds ratios (aOR) of variables associated with this outcome, controlling for clinical features, difficult airway characteristics, and ETI modality. Results: Of 15, 776 subjects who met selection criteria, 157 (1.0%, 95% CI 0.9–1.2%) experienced peri-intubation cardiac arrest. Pre-intubation systolic blood pressure <100 mm Hg (aOR 6.2, 95% CI 2.5–8.5), pre-intubation oxygen saturation <90% (aOR 3.1, 95% CI 2.0−4.8), and clinician-reported need for immediate intubation without time for full preparation (aOR 1.8, 95% CI, 1.2−2.7) were associated with higher likelihood of peri-intubation cardiac arrest. The association between pre-intubation shock and cardiac arrest persisted in additional modeling stratified by ETI indication, induction agent, and oxygenation status. Conclusions: Peri-intubation cardiac arrest for patients undergoing ETI in the ED is rare. Higher likelihood of arrest occurs in patients with pre-intubation shock or hypoxemia. Prospective trials are necessary to determine whether a protocol to optimize pre-intubation haemodynamics and oxygenation mitigates the risk of peri-intubation cardiac arrest.